Two Cases of Large Right Atrial Thrombus with Different Outcomes - Mukhamad, Sami Valid; MD,, Nadezda Zaytseva; Evgeni, Kudrashov (Journal of Surgery Proceedings, 2016)
Right atrial thrombi are a remarkable phenomenon especially when witnessed live on the monitor during echocardiographic study. They represent a clot en passant caught in the middle of travel to final destination in the pulmonary vasculature. In this paper we present two cases that show us the ambivalent nature of these clots, the challenges faced during their management and the possible outcome for the patient. The first case with fatal outcome is narrated in present tense because the outcome is fatal and the second is narrated in past tense because the patient survived and the clot became a past incidental encounter
Keywords: Echocardiography; thrombus; embolism; atrial; thrombolysis